ULASAN METODE JOB SAFETY ANALISIS (JSA) BERDASARKAN RISIKO KECELAKAAN KERJA DI PETIKEMAS MAKASSAR NEW PORT DALAM KONDISI BONGKAR MUAT - Asyikin AS, Muhammad Nur; Pradika, Dyo Abi; Nusul, Muhammad (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Activities at the container port are not without risk, for example the use of lifting and transporting equipment in the form of Rubber Tyred Gantry Crane (RTG) or Container Crane (CC) for loading and unloading operations, which is one of the reasons for the potential risk and high risk of work accidents. One way to mitigate potential risks and hazards is to first analyze the potential for work accidents using Job Safety Analysis (JSA) to minimize the possibility of work accidents in the loading and unloading process. The purpose of this study is to use JSA analysis to analyze the potential hazards and risks that occur at each stage of container loading and unloading operations and to determine the steps or procedures to manage the potential hazards and risks that occur at each stage of work. The benefits of this research are intended to be used as a basis and information about the hazards and risks of work accidents and the application of work safety analysis (JSA) as a risk assessment of work accidents in container loading and unloading and a reference for work accident risk management, especially in the stevedoring and haulage/tracking processes.